VR and computer vision based facade complexity analysis for building design - Fabian Jarrin; Yasuko Koga; Diego Thomas (Journal of Asian Architecture and Building Engineering)
Architectural practice is evolving through digital fabrication, enabling complex designs that challenge the uniformity of barren walls and fully glazed facades that often dominate contemporary streetscapes. This paper addresses the challenge of quantifying complexity in architectural facade design. It asks whether a Virtual Reality (VR) and Computer Vision (CV) approach can effectively measure facade complexity and align with user perceptions. The study employs the Computational Image Complexity Analysis (CICA) system, integrating VR and CV algorithms, to assess reactions to various facade complexities. Results reveal an average standard deviation of 9% between the system’s complexity measurements and participants’ perceptions, with a preference for moderate complexity. These findings highlight the importance of aligning architectural complexity with user preferences to enhance sustainability and satisfaction and the potential of this approach to quantify complexity and guide data-driven building design processes. Future research should explore the long-term impact of complex facades on user well-being and environmental sustainability.